Efektivitas Model Pembelajaran Group Investigation Terhadap Keaktifan dan Pemahaman Materi Siswa Pada Pelajaran Matematika - Jadidah, Nur Aulia; Sari, Sulistya Umie Ruhmana (Galois: Jurnal Penelitian Pendidikan Matematika, 2025)
The purpose of this study is to determine the effectiveness of the group investigation learning model on the activeness and understanding of student material in mathematics lessons. This research is a quasi-experimental research using a quantitative approach, while the design of this study is a pretest-posttest control group design, with a research population of class VII at MTs Negeri 1 Malang. The research sample is class VII G as an experimental class and class VII H as a control class. The result of this study is that the group investigation learning model is effective in student activity in mathematics lessons with the average pretest score is 77.97 and the average posttest score is 81.17. The group investigation learning model is effective in understanding student material in mathematics lessons with an average pretest score of 49.1 and an average posttest score of 84.1. The results of the calculation of the t-test of student activeness questionnaires and student material comprehension tests show that H0 rejected and Ha accepted, so it can be concluded that the application of the group investigation learning model is effective for the activeness and understanding of student material in mathematics lessons. Keywords: Numeracy Skills, Minimum Competency Assessment, Mathematics Learning. ABSTRAK Tujuan dari penelitian ini adalah untuk mengetahui efektivitas model pembelajaran group investigation terhadap keaktifan dan pemahaman materi siswa pada pelajaran matematika. Penelitian ini merupakan penelitian quasi experiment dengan menggunakan pendekatan kuantitatif, Adapun desain penelitian ini adalah pretest-posttest control group design, dengan populasi penelitian yaitu kelas VII di MTs Negeri 1 Malang. Sampel penelitian yaitu kelas VII G sebagai kelas eksperimen dan kelas VII H sebagai kelas kontrol. Hasil pada penelitian ini yaitu model pembelajaran group investigation efektif terhadap keaktifan siswa pada pelajaran matematika dengan nilai rata-rata pretest adalah 77,97 dan nilai rata-rata posttest adalah 81,17. Model pembelajaran group investigation efektif terhadap pemahaman materi siswa pada pelajaran matematika dengan nilai rata-rata pretest adalah 49,1 dan nilai rata-rata posttest adalah 84,1. Hasil perhitungan uji-t angket keaktifan siswa dan tes pemahaman materi siswa menunjukkan bahwa ditolak dan diterima, sehingga dapat disimpulkan bahwa penerapan model pembelajaran group investigation efektif terhadap keaktifan dan pemahaman materi siswa pada pelajaran matematika.